Comparing absolute lymphocyte count to total lymphocyte count, as a CD4 T cell surrogate, to initiate antiretroviral therapy - Srirangaraj Sreenivasan; Venkatesha Dasegowda (Journal of Global Infectious Diseases, 2011)
Background: The high cost of CD4 count estimation in resource-limited settings is a major obstacle in initiating patients on highly active antiretroviral therapy (HAART). Thus, there is a need to evaluate other less expensive surrogate markers like total lymphocyte count (TLC) and absolute lymphocyte count (ALC). Objectives : To evaluate the correlation of TLC and ALC to CD4 count. To determine a range of TLC and ALC cut-offs for initiating HAART in HIV-infected patients in resource-limited settings. Materials and Methods: In a prospective observational cohort study of 108 ART-naive HIV-positive patients, Spearman correlation between ALC and CD4 cell count, and TLC and CD4 cell count were assessed. Sensitivity, specificity, positive and negative predictive values of various ALC and TLC cut-offs were computed for CD4 count <200 cells/cu.mm. Results: Good correlation was noted between ALC and CD4 (r=0.5604) and TLC and CD4 (r=0.3497). ALC of 1400 cells/cu.mm had a sensitivity of 71.08% and specificity of 78.26% for predicting CD4 cell counts less than 200 cells/cu.mm. Similarly, TLC of 1200 cells/cu.mm had a sensitivity of 63.41% and specificity of 69.57%. Conclusion: Either ALC or TLC may be helpful in deciding when to initiate antiretroviral therapy in resource-poor settings, though ALC is better than TLC as a surrogate for CD4 counts.